New species of Lonchaeidae (Diptera: Schizophora) from central and southern Africa - Macgowan, Iain (Zootaxa, 2005)
Eleven new species of Lonchaeidae are described, namely, Lamprolonchaea longicercus MacGowan sp. nov. (Tanzania), Lonchaea asymmetrica MacGowan, sp. nov. (Tanzania), Lonchaea grandiseta MacGowan, sp. nov. (Botswana & Namibia); Silba budongo MacGowan sp. nov (Uganda) , Silba calceus MacGowan, sp. nov. (Namibia); Silba figurata MacGowan sp. nov (Uganda), Silba gongeti MacGowan sp. nov (Uganda), Silba namibia MacGowan, sp. nov. (Namibia), Silba quadridentata MacGowan, sp. nov. (Uganda), Silba spatulata MacGowan, sp. nov. (Tanzania) and Silba uganda MacGowan sp. nov (Uganda) The previously unknown male of Lonchaea haplosetifera McAlpine is also described from South Africa. New records of Lonchaeidae species are provided for Botswana, Namibia, Tanzania and Zambia.